CHEMICAL AND ORGANOLEPTIC PROPERTIES OF BEKAI (Pycnarrhena tumefacta Miers) LEAVES FOR FLAVOURING AGENT (BIO-VETSIN) - Maharani, Rizki; Fernandes, Andrian; Turjaman, Maman; Kuspradini, Harlinda; Lukmandaru, Ganis (Association of Indonesian Forestry and Environment Researchers and Technicians, 2020)
The